Wounding causes rapid, intense upregulation of glycolytic and fermentative genes and enzymatic activities in harvested sugarbeet roots - Karen K. Fugate; Mercedes Morin; John D. Eide; Abbas M. Lafta; Fernando L. Finger (Scientific Reports, 2025)
Abstract Sugarbeet roots are severely wounded during harvest, triggering wound-healing responses to seal off and defend damaged cells. Primary carbon metabolism is required to provide metabolic energy and substrates for wound healing processes, yet how wounding alters primary carbon metabolism is largely unstudied in sugarbeet or other plant species. Wound effects on primary carbon metabolism were determined in the 24 h following injury by evaluating changes in gene expression and enzymatic activities of primary carbon metabolic pathways. Wounding significantly altered expression of 43 primary carbon metabolic pathway genes including 3, 19, 3, 7, and 9 genes involved in sucrolysis, glycolysis, TCA cycle/organic acid metabolism, pentose phosphate pathway, and fermentation, respectively. Highly upregulated genes were involved in sucrolysis, glycolysis, and fermentation, although only enzymatic activities of glycolytic and fermentative enzymes were majorly increased. The results indicate that wounding rapidly upregulates glycolysis and fermentation, with minimal effect on sucrolysis, the TCA cycle and the pentose phosphate pathway. We propose that glycolysis has a dominant role in controlling and upregulating carbon metabolism to support wound healing in postharvest sugarbeet roots, independent of elevations in sucrose catabolism or the TCA cycle, and fermentation is intensely upregulated to maintain glycolytic flux due to the insufficient activity of the TCA cycle to metabolize glycolytic end-products.